Tinjauan Yuridis terhadap Fungsi dan Kewenangan Legislasi Dewan Perwakilan Daerah (DPD) dalam Sistem Parlemen Bikameral (Dua Kamar) Negara Republik Indonesia - Fandy Gultom; Iswanti Rachmanisa; Vedita Akbar; Nada Prima Dirkareshza; Bayu Aji Adhyarsa; Handoyo Prasetyo; Atik Winanti (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
In the process of forming a law or legislation, the DPD does not have the power to decide or play a role in the decision-making process at all. Even though there are support requirements to become a member of the DPR. This means that the quality of the legitimacy of DPD members is not at all balanced by the quality of their authority as representatives of the regional people. The aim of this research is to analyze the function and authority of the Regional Representative Council in the Structural Institution of the Republic of Indonesia State Legislative Institution and how to optimize the function and legislative authority of the Regional Representative Council. The type of research we use is normative legal research, namely research carried out by examining the body of literature or secondary data. Strengthening the authority of the DPD by consistently incorporating the Constitutional Court's decisions into statutory regulations and other regulations under it. This is being done pending the issuance of the fifth amendment to the 1945 Constitution. The current revision of the MD3 Law has not yet adopted the authority of the DPD in accordance with the Constitutional Court's decision. The need for the fifth amendment is to reorganize the function of legislation firmly and clearly in the 1945 Constitution, because by reorganizing the function of legislation it will touch all institutions, including the DPR, DPD, President and other institutions.